Fractional order differentiation and robust control design : CRONE, H-infinity and Motion Control /: CRONE, H-infinity and Motion Control. ([2015]) - Sabatier, J (Jocelyn); Lanusse, Patrick; Melchior, Pierre; Oustaloup, Alain
No abstract available